Internal Mammary Artery Compression After Pectus Excavatum Repair Does Not Increase Risk of Hemorrhagic Complications in Pediatric Patients - Kovács, Tamás; Pásztor, Gyula; Rieth, Anna (Frontiers in Pediatrics, 2021)
Objectives: Minimal invasive repair of pectus excavatum (MIRPE) described by Nuss is the most popular correction nowadays of this deformity. During the introduction of the bars, they can hurt or compress the internal mammary arteries (IMA). The aim of this study was to observe the prevalence of IMA compression in children after MIRPE. Also, we examined if IMA obstruction increases the risk of complications at bar removal, and if these vascular changes are reversible. Materials and Methods: All patients operated on pectus excavatum in our tertiary pediatric surgical center between 2013 and 2019 were involved in the study. Data of age, sex, number of bars and characteristics of the deformity were examined. IMA flow was checked by Doppler ultrasound (DUS) after MIRPE and after bar removal, too. Results: Among 41 patients with mean age of 15.2 years there were 18 asymmetrical deformities, 23 sternal rotations. Mean pectus index was 4.01. After the Nuss procedure 7(9%) stenoses and 10(12%) occlusions of IMA were found on DUS. After bar removal 3 of 4 stenoses have resolved, but all examined occlusions (3/3) persisted. There were no complications during bar removals. Conclusion: IMA compression after MIRPE in children is uncommon, and is not influenced by severity of deformity. Obstruction of these vessels does not increase the risk of hemorrhagic complications at bar removal. Data of larger cohort are needed to determine reversibility of these changes.